Exploring Students’ Perceptions of Learning Medical Terminology With Teacher-Made Flashcards Used Electronically - Iman Alizadeh; Farideh Ebrahimi; Afsane Dehnad (Acta Medica Iranica)
Although the production and use of educational materials have been accelerated, their quality and usability for students might have been overshadowed by the urgency to maintain the continuity of education at universities. Concerned with the provision of quality education, this study aimed to discover medical sciences students’ perceptions of the quality of teacher-made medical terminology flashcards used in university courses electronically. To do so, the students in the fields of laboratory sciences, radiology, anesthesia, operating room, nursing, medicine, and midwifery used the teacher-made flashcards in medical terminology and specialized English courses, and their perceptions of the quality of the flashcards were elicited in terms of appearance, content of information, and potential contribution to learning. The results showed that overall, the students evaluated the flashcards positively; they, however, indicated that the color choices, adequacy of information, and potential effects on students’ motivation for studying medical terms were three aspects of the flashcards that warranted more detailed consideration. Moreover, the students’ perceptions of the appearance of the flashcards and the potential contribution of the flashcards to learning did not differ across the disciplines; the students, however, had different perceptions of the content of information on the flashcards due to the type, degree, and specificity of the information they needed. The study concludes that how the flashcards are developed aesthetically, how exhaustively they embrace the students’ needs for information, and how potentially efficaciously they contribute to learning mattered to the students. The study recommends that although teacher-made materials can support the delivery of knowledge and continuity of education, considering students’ feedback on and perceptions of the materials can help secure the quality and usability of the materials and ensure quality teaching and learning.